2017
DOI: 10.14355/bab.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Study of Novel Schiff Bases and Metal Complexes

Abstract: Novel Schiff bases (E)-6-(benzylideneamino)-3,3-dimethyl-7-oxo-4-thia-1-aza-bicyclo heptane-2-carboxylic acid (L1) and (E)-6-(4-hydroxy benzylideneamino)-3,3-dimethyl-7-oxo-4-thia-1-aza-bicyclo heptane-2-carboxylic acid (L2) were synthesized. Further metal complexes of these Schiff bases were synthesized using various metal nitrates. Both Schiff bases and their metal complexes were screened for antibacterial activity against different bacterial species such as Escherichia coli, Pseudomonas aeruginosa and Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Thus, the ability of antibiotics to kill or inhibit the growth of bacteria is may be through inhibition of a step in peptidoglycan synthesis by gram positive bacteria. 47,48 In the case of antibacterial activity against Gram-positive bacteria (S. aureus and Bacillus), all compounds were found to have activity ranged between high and moderate. Our results indicated that the compounds Z 3 C and Z 3 C' possessed the highest antibacterial activity against Gm +Ve (S. aureus) with an IZ of (20, 22, 23, 25 and 21, 22, 26, 30 mm) at concentrations of (5, 25, 125, 250 mg/mL), respectively.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Thus, the ability of antibiotics to kill or inhibit the growth of bacteria is may be through inhibition of a step in peptidoglycan synthesis by gram positive bacteria. 47,48 In the case of antibacterial activity against Gram-positive bacteria (S. aureus and Bacillus), all compounds were found to have activity ranged between high and moderate. Our results indicated that the compounds Z 3 C and Z 3 C' possessed the highest antibacterial activity against Gm +Ve (S. aureus) with an IZ of (20, 22, 23, 25 and 21, 22, 26, 30 mm) at concentrations of (5, 25, 125, 250 mg/mL), respectively.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The results may give an indication about the moderate toxicity effect of the studied compounds and clinical change observed in the mice after giving different doses. The toxic observed in injected mice may be manifested in some behaviors such as tremors, straight tail, salivation, urination, lacrimation, defecation, shortness of breath, excitation, muscle fasciculations, capillary bulge, convulsions and also the tortuous reflex in some treatments, and finally death at high toxic doses, Table 2 [40][41].…”
Section: Biological Activitymentioning
confidence: 99%
“…Thus the ability of antibiotics to kill or inhibit the growth of bacteria is may be through inhibition of a step in peptidoglycan synthesis by gram positive bacteria. [42,43] In the case of antibacterial activity against Grampositive bacteria (Staphylococcus aureus and Bacillus), all compounds were found to have activity ranged between high and moderate. Our results indicated that the compound Z5A11'possessed the highest antibacterial activity against Gm+Ve (Staphylococcus aureus) with an IZ of (10, 23, 29, 30, and 31 mm) at concentrations of (1, 5, 25, 125, 250 mg/mL).…”
Section: Antibacterial Activitymentioning
confidence: 99%